Explore BrainMass
Share

Explore BrainMass

    Compute the uncertainty product for a harmonic oscillator

    This content was COPIED from BrainMass.com - View the original, and get the already-completed solution here!

    See attached file.

    © BrainMass Inc. brainmass.com October 9, 2019, 9:21 pm ad1c9bdddf
    https://brainmass.com/physics/heinsenburgs-uncertainty-principle/compute-the-uncertainty-product-for-a-harmonic-oscillator-181446

    Attachments

    Solution Preview

    Notation: If A is an operator then I'll denote the Hermitian conjugate of A by C(A)

    The annihilation operator in terms of p and x is:

    a = 1/sqrt(2m hbar omega) [m omega x + i p]

    And the creation operator is its Hermitian conjugate:

    C(a) = 1/sqrt(2m hbar omega) [m omega x - i p]

    It is convenient to have the expressions for x and p in terms of a and C(a). Solving the above equations for x and p gives:

    x = Squareroot[h-bar/(2 m omega)] [a + C(a)]

    p = i Squareroot[m omega h-bar/2] [C(a) - a]

    The Hamiltonian is:

    H = [C(a) a + 1/2] hbar omega

    a and C(a) satisfy the commutation relation:

    [a, C(a)] = 1 (1)

    We also have:

    [H, a] = [[C(a) a + 1/2] hbar omega, a] = hbar omega [C(a) a, a] = hbar omega [C(a)a a - a C(a) a ]

    From (1) it follows that a C(a) = 1 + C(a) a. The second term in the above formula can thus be written as:

    a C(a) a = [1 + C(a) a] a = a + C(a) a a

    The expression for the commutator thus simplifies to:

    [H, a] = -hbar omega a (2)

    We can compute the eigenvectors and eigenvalues of H as follows. We put C(a) a = N. Then since H = hbar omega(N+1/2)
    we can just as well compute the eigenstates of N. These are then also the eigenstates of H. If |n> is a normalized eigenstate of N with eigenvalue n, then N|n> = n|n> and thus H|n> = (n+ 1/2)hbar omega|n>, so the corresponding eigenvalue of H is
    (n + 1/2)hbar omega. Note that we are not assuming that n is an integer.

    Consider the action of N on the state a|n>:

    N a|n> = C(a) a a|n>

    Eq. (1) says that

    a C(a) - C(a) a = 1 ------>

    C(a) a = a C(a) - 1

    and we see that

    N a|n> = C(a) a a|n> = [a C(a) - 1]a |n> = a C(a) a|n> - a|n> = a N|n> - a|n> = n a |n> - a |n> = (n-1)|n> (3)

    So, it looks like a|n> is an eigenstate with eigenvalue n-1. Let's compute the norm of this state. The absolute value squared of the norm is:

    <n|C(a) a|n> = <n|N|n> = <n|n|n> = n <n|n> = n. (4)

    The absolute value squared of any ...

    Solution Summary

    A detailed solution is derived from first principles.

    $2.19